The Emergence and Historical Development of Informatics and Computing Disciplines in Selected European Countries and the USA - Zdeněk Smutný; Michal Doležel (Acta Informatica Pragensia, 2017)
This article presents an overview that compares the historical tendencies in defining informatics as a new discipline, subject area or field of study focused on the design and application of computer technology. Apart from computer construction, the focus is on two major areas: computational processes and information processes. The article first considers the development in the United States of America (USA), which differed substantially from Europe. In the USA the development concerned disciplines referred to as computer science, computer engineering and (library and) information science. The article then discusses the situation in France and Germany. Consequently, the development in the USA and Western Europe is contrasted with the development in the Soviet Union, particularly with the crucial role of cybernetics in this region. The time range considered in the article is limited to the 1960s and 1970s. The article introduces the individual regional concepts of informatics and discusses the social, economic and political background of the emergence and development of these concepts. This view makes it possible to present an original approach to the ambiguous interpretation of “What is informatics as a scientific discipline in an international context”, while respecting the distinctions given by the outset and historical development in different countries.